(untitled) (Dhaka University Journal of Biological Sciences, 2026)
Microplastics (MPs) are among the emergent contaminants that have attracted increasing global concern in recent years. These particles are now pervasive across nearly all ecological compartments, posing substantial risks to both environmental integrity and human health. This study investigated the MPs contamination in commonly consumed fish species from an ecologically critical river in Bangladesh, the Halda. The MPs particles in muscle (including skin) and gastrointestinal tract (GIT) of fish were extracted using H2O2 digestion followed by density separation. Across the species, per individual abundance of MPs was higher in GIT (6.5 ± 3.6 particles/individual) than that of muscle (6.1 ± 3.3 particles/individual). Apparent higher concentration of MPs in GIT and muscle of herbivores (9.0 ± 2.9 and 5.8 ± 2.6 particles/individual, respectively) coupled with lower MPs abundance in carnivores (6.8 ± 2.7 and 4.2 ± 1.8 particles/individual in GIT and muscle, respectively) suggested that the pelagic food source is likely to be the primary pathway of MPs accumulation in the Halda river fishes. Contrastingly, lower MPs accumulation in carnivores and insignificant correlation between fish size and MPs abundance suggested biomagnification of MPs was not substantial. Therefore, it was evident that MPs contamination in fish of this river was spatially dispersed due to heterogenous sources along the river course. Among the identified MPs, fiber-shaped and small-sized ones (<500µm) were the most prevalent. The ATR-FTIR spectroscopy revealed that Polypropylene constituted the major proportion indicating potential high MPs discharge by domestic and textile industries. This study suggests that Halda river is polluted with MPs which could ultimately pose health risks to humans through fish consumption. Dhaka Univ. J. Biol. Sci. 35(1): 17-35, 2026 (January)